Action of Metal and Organometallic Halides and Pseudohalides Towards Stannoxanes - Singhal, Kiran; Kumar Chaudhary, Subhas; Prakash, Om (Asian Journal of Chemistry, 2013)
Interactions of HgX2 (X = Cl, Br, I, SCN, CN, NCO), SbCl3, TeCl4 and PhTeCl3 with (p-FC6H4)3Sn-O-Sn(p-FC6H4)3 at room temperature have been found to proceed with the simultaneous cleavage of Sn-O and Sn-C bonds, invariably yielding (p-FC6H4)2SnO, (p-FC6H4)3SnX and the corresponding organo-mercury, -antimony and -tellurium derivatives. The course of the reactions suggests the instability of the Sn-O-M (M = Hg, Sb, Te) system.